Peace-making and propaganda: an examination of alternate succession as a means of justification and consolidation of power in early medieval Ireland, c. 500-1000 - Macauliffe, Hannah (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2025)
This thesis is an examination of the role and function of alternate succession as it existed in early medieval Ireland, as well as in areas of Irish influence in Scotland. Alternate succession refers to a phenomenon whereby kingships were shared alternately between two or more eligible branches of a royal dynasty, in a back-and-forth pattern. Patterns of the like appear across early medieval Ireland and Scotland, in the kingships of Munster, Leinster, Dál Riata and the Northern Uí Néill, and it is most famously associated with the kingship of Tara, where power seems to have alternated between the Northern and Southern branches of the Uí Néill dynasty. Despite its apparent prevalence in the early medieval Irish world, a dedicated study of the phenomenon has yet to be produced. This thesis aims to fill this gap in the scholarship. Through a comparison of the king lists, annals, genealogical material, and inventive literature, this thesis aims to better understand the place of alternate succession in the practice of Irish kingship. In examining each of the previously-mentioned kingships, as well as their relationships with each other and with the early Christian church in Ireland, this thesis will demonstrate that the purpose of alternate succession was two-fold. On one hand, it was a form of power-sharing, and served to create stability in kingdoms by promoting peace and alliance among the branches of a royal dynasty in the face of external pressures. On the other hand, it was an effective tool of medieval propagandists, and served to justify and consolidate claims to power.
APPROVED
Keywords: Power; Kingship; Alternate Succession; Social Order; Dynastic Politics; Succession; Medieval Ireland